Hydrogen production by dark fermentation process from pig manure, cocoa mucilage, and coffee mucilage (2020)
The aim of this study was the evaluation of the influence of temperature, initial organic load, and C/N ratio in the biochemical hydrogen potential (BHP) by dark fermentation (DF) of mixtures composed of residual biomass derived from the Colombian agro-industry (pig manure, cocoa mucilage, and coffee mucilage) to contribute to residue management and the development of a bio-based economy in Colombia. A Box-Behnken experimental design was constructed, where the variables were as follows: three initial organic loads (2, 5, and 8 g COD/l), three C/N ratios (25, 35, and 45), and three different coffee and cocoa initial COD ratios (coffee mucilage (CFM):cocoa mucilage (CCM)) (1:3, 2:2, and 3:1). The experiments were carried out at thermophilic environments of 55 °C and 45 °C. Sludge from an anaerobic digester pretreated by thermal shock was used as an inoculum. The results of the experimental designs were used (one per temperature) to model the system mathematically. Also, a mathematical model MARS (multivariate adaptive regression splines) was used as an alternative method to corroborate the optimal points obtained. In both models, it was evidenced that at 55 °C and 45 °C, the best mixing conditions indicated a C/N ratio of 45 and the lowest CFM:CCM with a value close to 1:3. Likewise, it was evidenced that at the temperature of 55 °C, the optimum organic load is 8 g COD/l, while 45 °C is 2 g COD/l. Moreover, it was determined that CFM:CCM has less influence than the other independent variables studied, a factor that favors the country’s scope, due to the availability of these two substrates is not permanent throughout the year. © 2020, Springer-Verlag GmbH Germany, part of Springer Nature.